THE ALGORITHM TO CALCULATE THE ORDINATES OF THE INFLUENCE LINES FOR THE EXPERIMENTAL DATA - Suhorukov, B. D. (Science and Transport Progress, 2008)
A computational algorithm for determining the ordinates of full-scale influence line was suggested and performed using the loading oscillograms of the bridge constructions under effect of the slowly moving test load..